HUBUNGAN ANTARA KEDISIPLINAN DAN MOTIVASI BELAJAR SISWA DENGAN PRESTASI BELAJAR SISWA SEKOLAH DASAR DI GUGUS NGAMPILAN - Rafif Arkhab Kurniawan; Heru Susanto, Bahtiyar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between learning discipline and learning motivation on the academic achievement of fifth-grade students at SD Negeri Kembanglangit. This research employed a quantitative approach using a correlational method. The population consisted of all fifth-grade students at SD Negeri Kembanglangit, totaling 30 students. A saturated sampling technique was applied, in which all members of the population were selected as research participants. Data were collected through questionnaires measuring learning discipline and learning motivation, as well as documentation of students' academic achievement scores. The data were analyzed using prerequisite tests, including normality, linearity, and multicollinearity tests, followed by Pearson correlation analysis and multiple linear regression analysis. The findings revealed a positive and significant relationship between learning discipline and students' academic achievement, a positive and significant relationship between learning motivation and academic achievement, and a positive and significant simultaneous relationship between learning discipline and learning motivation on students' academic achievement. These findings indicate that higher levels of learning discipline and motivation are associated with better academic achievement.